PEMENUHAN JAMINAN KESEHATAN OLEH PERUSAHAAN DALAM PERPEKTIF PERATURAN PEMERINTAH NOMOR 86 TAHUN 2013 - Luhukay, Roni Sulistyanto (Universitas Djuanda, 2021)
Fulfillment of workers' rights to health is a basic right guaranteed by the state, this is because health as an element of general welfare must be realized in accordance with the aspirations of the Indonesian people, this welfare is in the form of health which must receive protection from the government Health must be fulfilled legally and constitution. For this reason, the fulfillment of workers' rights to obtain health insurance provides social protection for workers in order to increase their welfare and productivity. The BPJS Health Insurance by the Company is a state step in guaranteeing the workers' Health Insurance through the BPJS program with the intention that this obligation can cause optimal losses from the company without considering other aspects. The act of requiring companies to register themselves with the BPJS also killed other businesses that were engaged in business activities. Ideally, the government is present as part of providing revolutionary breakthroughs by not involving the interests of other institutions, the responsibility of the state is to protect every business activity and not to compete with or prioritize certain institutions but to be able to show objectivity and fairness in every business activity.